A Novel, Sterilized Microvascular Tissue Product Improves Healing in a Murine Pressure Ulcer Model. Issue 11 (November 2018) - Gimble, Jeffrey M.; Frazier, Trivia; Wu, Xiying; Uquillas, Andrea Alarcon; Llamas, Claire; Brown, Theodore; Nguyen, Doan; Tucker, H. Alan; Arm, Douglas M.; Peterson, Dale R.; Bunnell, Bruce A.
Abstract : Background: Processed microvascular tissue (PMVT), a human structural allograft, is derived from lyophilized human tissue containing microcirculatory cellular components. Since PMVT serves as a source of extracellular matrix (ECM), growth factors, cytokines, and chemokines modulating angiogenesis, inflammation, apoptosis, and endogenous cell recruitment, we hypothesized its application would accelerate wound regeneration in a validated pressure ulcer (PU) model developed in C57BL/6 mice using two 24-hour cycles of skin ischemia/reperfusion created by placement and removal of external magnets. Methods: Two identical PU injuries (n = 50 female mice) were treated with (a) topical particulate PMVT, (b) injected rehydrated PMVT, or (c) saline control injection, and assessed daily for closure rates, scab formation/removal, and temperature. A baseline control cohort (n = 5) was euthanized at day 0 and treatment group cohorts (n = 5) were killed at 3, 7, or 14 days postinjury. The PU injuries were collagenase-digested for flow cytometric analysis of inflammatory, reparative, and stem cell frequencies and analyzed by hematoxylin and eosin (H&E) histology and immunofluorescence. Results: PMVT-accelerated wound closure, most notably, topical PMVT significantly increased mean closure from d5 (13% versus -9%) through d13 (92% versus 38%) compared with phosphate-buffered saline (PBS) controls ( P < 0.05). PMVT also hastened scab formation/removal, significantly accelerated disappearance of inflammatory myeloid (CD11b+) cells while upregulating α-smooth muscle actin, vascular endothelial growth factor A, and placental growth factor and raised skin temperature surrounding the PU site, consistent with increased blood flow. Conclusions: These results indicate that PMVT has potential as an advanced treatment for restoring normal tissue function in ischemic wounds and merits clinical study.